The nominales, Sempiternal Truth, and Tensed Propositional Contents - Wciórka, Wojciech Jerzy (Vivarium, 2024)
This article distinguishes between two historical ways of presenting the catchphrase “Once true, always true” (semel verum, semper verum), associated with the twelfth-century logical school of the nominales. Within the Time-Jumping Model, a hypothetical tenseless propositional content (enuntiabile) is treated as the common significate of differently tensed statements, such as “Socrates will die” and “Socrates died,” uttered before and after Socrates’s death. This hypothetical enuntiabile is “always true” thanks to its tenseless nature. By contrast, the Fixed-Present Model preserves the tensed character of enuntiabilia. By revealing an implicit temporal index, the nominales could apply “Once true, always true” to enuntiabilia such as Christum venisse (that Christ has come), which not only is true and will always be true but also – paradoxically – has always been true. It has always been true because it amounts to the propositional content that Christ came before this instant, where “this instant” rigidly denotes the present moment. The Fixed-Present Model alleviates the worry that the nominales confused truth-bearers with truthmakers.